Kinetic of Biogas Production in a Batch Anaerobic Digestion Process with Interference of Preservative Material of Sodium Benzoate - Indro Sumantri; Hadiyanto Hadiyanto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Sodium benzoate is a preservative compounds which are widely used for both food and beverage products. The treatment of waste water containing this compound was normally conducted in a anaerobic digestion (AD) using a batch reactor system at a room temperature. The anaerobic process eventually produced biogas which can be used for bioenergy. This research was aimed to evaluate the production of biogas from by synthetic solution models containing sodium benzoate (SB). The experiment was performed in a variation of Mixed Liquor Suspended Solid (MLSS) of 4.8 and 7.2 g/L, and initial sodium benzoate concentration of 400, 600, and 800 mg/L. The digestion was performed at 60 days, while the biogas content was measured every 2 days. The results indicated a reduction in the cumulative biogas by the addition of sodium benzoate, compared to the control condition. Moreover, the decrease in organic loading rate (OLR) of SB in wastewater follows the first order kinetic with kinetic rate constant (k) was 0.0432 to 0.1254 (day−1) for MLSS of 4.8 g/L and 0.0276 to 0.0372 (day−1) for 7.2 g/L MLSS. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).